BREAST CANCER STEREOTACTIC BIOPSY UNDER X-RAY CONTROL - Akhmadova Maftun Amin kizi (Scholars Digest Publishing, 2023)
The issue of the diagnosis of aggressive carcinomas of small size is relevant and timely all over the world, which served as the basis for this study to search for the most characteristic radiological and sonographic signs of microcarcinomas in patients with different biological subtypes of breast cancer. Accumulated by radiation diagnosticians over the past decades, in some cases, the interpretation of the changes detected during mammography is difficult. the possibility of performing stereotactic biopsy of mammary gland formations under X–ray control is one of the important factors for the successful operation of the outpatient polyclinic of a specialized oncological institution. the article presents more than 15 years of experience in performing stereotactic biopsy of mammary gland formations under X-ray control.
Keywords: stereotactic biopsy, breast cancer, mammography.